Aggressive Differentiated Thyroid Cancer due to EML4e13-ALKe20 Fusion: A Case Presentation and Review of the Literature - Rodhan Khthir; Zainab Shaheen; Prasanna Santhanam; Saroj Sigdel (Case Reports in Endocrinology)
Background. Differentiated thyroid cancer (DTC) is an indolent malignancy. It rarely presents with aggressive local invasion and/or distant metastatic disease. Patient findings. We describe a case of a 30-year-old man with a locally aggressive form of papillary thyroid cancer with EML4e13-ALKe20 fusion (EML4: echinoderm microtubule-associated protein-like 4; ALK: anaplastic lymphoma kinase). He presented with right-side cervical lymphadenopathy with a highly suspicious right-side thyroid nodule. Total thyroidectomy and level IV lymph node resection showed extensive bilateral disease, with extrathyroidal and extranodal extension. FDG-PET CT scan following surgery confirmed the presence of significant residual disease in the neck area. He underwent bilateral lateral lymph node dissection followed by radioactive iodine treatment. Somatic mutation testing showed EML4e13-ALKe20 fusion. Summary. This case represents an aggressive form of DTC with EML4e13-ALKe20 fusion. The rapid progression of clinical signs and symptoms and the local extension beyond the thyroid and lymph nodes with the persistence of high-volume local disease after thyroidectomy highlight the aggressive nature of this mutation and the importance of performing genetic analysis to guide future treatments and determine prognosis. Conclusion. This case highlights the importance of using molecular diagnostics in patient care, especially if the presentation is unusual for DTC. A thorough evaluation of the tumor pathology and the somatic mutational profile analysis are important for obtaining vital therapeutic and prognostic guidance.